2019
DOI: 10.1096/fasebj.2019.33.1_supplement.783.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrogen Peroxide on Hydrolysis of Proteins

Abstract: Hydrogen peroxide (H2O2) is the active ingredient in over‐the‐counter whitening strips for teeth. It has previously been shown to damage certain proteins by making them more susceptible to hydrolysis by proteases. The goal of this project was to characterize the hydrolysis of various proteins with H2O2. Albumin protein was mixed with different concentrations of H2O2 for one hour. The protease trypsin was added and portions were removed and immediately mixed with trichloroacetic acid to precipitate either unhyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Although the reason for this is unclear, tooth bleaching methods can change the abundance of proteins in the gingival crevicular fluid 42 , which accumulates in the necks of teeth 43 . Since proteins are built by blocks of amino acids, the use of whitening peroxide-based products could cause the hydrolysis of proteins 44 present in teeth samples. This is consistent with the higher concentration of free amino acids and dipeptides after dental whitening treatments (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although the reason for this is unclear, tooth bleaching methods can change the abundance of proteins in the gingival crevicular fluid 42 , which accumulates in the necks of teeth 43 . Since proteins are built by blocks of amino acids, the use of whitening peroxide-based products could cause the hydrolysis of proteins 44 present in teeth samples. This is consistent with the higher concentration of free amino acids and dipeptides after dental whitening treatments (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Keenan et al investigated the effects of whitening agents on proteins related to dentin. They found that the major protein in dentin was converted to smaller fragments following treatment with hydrogen peroxide. Collagen is the main protein that composes 90–95% of dentin . Thus, some studies have focused on the degradation of collagen by tooth-whitening agents. , For example, Liu et al investigated changes in collagen properties, such as morphology, structure, and mechanical properties, by applying hydrogen peroxide .…”
Section: Side Effects Of Tooth Whiteningmentioning
confidence: 99%